A wall self-repairing method based on self-repairing polymer cement waterproof coating

By using layered hydrotalcite with complex loading in polymer cement waterproof coatings, pyrogenic gallic acid is released at the damaged area and an oxidation reaction occurs, the polymer in the prior art is solved by using the action of water and OH- The problem of insufficient self-repairing ability of cement waterproof coatings has achieved self-repair of 0.7mm wide cracks, maintaining the integrity and waterproof performance of the coating film.

CN114961145BActive Publication Date: 2025-01-14SHANGHAI WEIXING KALE NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210560516.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-01-11
Publication Date
2025-01-14
Estimated Expiration
2041-01-11

AI Technical Summary

Technical Problem

The existing polymer cement waterproof coatings lack self-repairing capabilities after damage, resulting in inconvenience in construction.

Method used

Using self-repairing method based on self-repair polymer cement waterproof coating, by using layered hydrotalcite with complex loading in the coating, pyrogenic gallic acid at the damaged area under the action of water and high concentration of OH- Release and oxidize with oxygen to form benzenequinone structure and ettringite crystals, filling the gaps to repair the cracks.

Benefits of technology

Under certain conditions, it can self-repair cracks with a width of 0.7mm to maintain the integrity and waterproof performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114961145B_ABST
    Figure CN114961145B_ABST
Patent Text Reader

Abstract

The present invention discloses a wall self-repairing method based on a self-repairing polymer cement waterproof coating, step one, coating molding, according to the liquid component and the solid component according to the mass ratio of 1: 1.5 ~ 1: 2.5 for proportioning, stirring evenly after molding; step two, brushing, the above-mentioned coating is covered and brushed on the surface to be constructed, and a coating layer is formed after drying; step three, aging damage, the coating layer is in contact with water and high concentration of OH-infiltrated after damage, and the complex loaded in the layered hydrotalcite is released under the action of water and high concentration of OH~ to form an oxidation reaction, and a polymerization is formed to complete the repair and filling of the damaged part. The polymer cement waterproof coating of the present invention uses organic and inorganic repair agents, which can maintain the self-repairing effect of the coating to the greatest extent, and can self-repair cracks with a width of 0.7mm under certain conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building waterproofing, and in particular relates to a wall self-repairing method based on a self-repairing polymer cement waterproof coating. Background Art

[0002] In recent years, polymer cement waterproof coatings have been widely used in various waterproof projects, such as bathrooms, basements, roofs, pools, tunnels, etc. This type of waterproof coating can meet the requirements of different construction sites for coating strength and flexibility by adjusting the ratio of cement and polymer emulsion. However, when the coating is damaged, it is often necessary to destroy the protective decorative layer covering it for maintenance, which brings great inconvenience to the construction.

[0003] Self-repairing waterproof coating can solve the above pain points. It can imitate human skin and self-heal and automatically repair leaks after the coating is damaged, thereby ensuring the integrity of the waterproof coating and the safety of the entire waterproof system. Self-repairing polymer cement waterproof coating can better resist cracking and deformation of the base layer due to its good self-closure, strong stability and high safety. It quickly captures the psychology of customers and will surely become a hot spot in the market.

[0004] Hydrotalcite compounds (LDHs) are a kind of inexpensive and easy-to-prepare anionic layered compounds. The typical molecular formula of hydrotalcite is Mg6Al2(OH) 16 CO3·4H2O. The atoms on the main layers of hydrotalcite are mainly connected by covalent bonds, and the main layers and interlayer anions are mainly connected by ionic bonds, hydrogen bonds, and van der Waals forces. Therefore, the binding force between the layers and the interlayer anions is relatively weaker and easier to break. When replaced with other anions, the guest anions between the layers are freed, and this replacement will not change the structure of the main layers of hydrotalcite. Only the interlayer spacing will change. Therefore, this characteristic of hydrotalcite can be used to load compounds with self-repairing functions between the layers of hydrotalcite. When the external environment changes, such as humidity, pH, etc., the self-repairing functional compounds loaded between the hydrotalcite layers can be gradually released, and a cross-linking reaction occurs, thereby completing the self-repair of the damaged parts. Summary of the invention

[0005] In order to solve the problem that the existing polymer cement waterproof coating has insufficient self-repairing ability after damage, the present invention provides a wall self-repairing method based on a self-repairing polymer cement waterproof coating, which can self-repair cracks as wide as 0.7 mm in a humid environment.

[0006] The technical solution of the present invention is as follows:

[0007] A wall self-repairing method based on a self-repairing polymer cement waterproof coating, step one, coating molding, according to the liquid component and the solid component according to the mass ratio of 1:1.5 to 1:2.5, stirring evenly and then molding; step two, brushing, the above coating is covered and brushed on the surface to be constructed, and a coating layer is formed after drying; step three, aging damage, the coating layer and the water penetrated after the damage, high concentration of OH - In contact, the complex supported in the layered hydrotalcite is exposed to water and high concentration of OH — Under the action of, the oxidation reaction is released, and then polymerization is formed to complete the repair and filling of the damaged area.

[0008] Based on the above, the liquid component includes the following substances in mass percentage: 80%-95% acrylic emulsion, 0.1%-1% sodium salt dispersant, 0.2%-0.5% wetting agent, 0.1%-1% propylene glycol, 0.1%-0.5% defoaming agent, and the balance is water; the solid component includes the following substances in mass percentage: 10%-30% heavy calcium, 20%-50% quartz sand, 2%-10% calcium sulfoaluminate type expansion agent, 1%-10% modified hydrotalcite, and the balance is cement.

[0009] Based on the above, the modified hydrotalcite adopts layered hydrotalcite loaded with a complex, wherein the complex is formed by pyrogallic acid and borate.

[0010] Based on the above, the acrylic esters and the emulsion are at least one of styrene acrylic emulsion, pure acrylic emulsion, styrene butadiene emulsion, and silicone acrylic emulsion.

[0011] Based on the above, the wetting agent is a polyoxyethylene ether surfactant.

[0012] Based on the above, the particle size of the quartz sand is at least one of 70-140 meshes or 100-200 meshes.

[0013] The self-repairing principle of the present invention is as follows: During the drying and film-forming process of the polymer cement waterproof coating, the complex pyrogallic acid loaded on the hydrotalcite can be stably stored in the system in large quantities due to the slow release effect. When the dried coating film is damaged, leakage occurs at the cracks. At this time, in the presence of water and high concentration of OH - Under the action of pyrogallic acid, the complexed pyrogallic acid is gradually released from the hydrotalcite. Since the phenolic hydroxyl group of pyrogallic acid has high activity, it can react with water, oxygen, etc. in the system to form a quinone structure, and produce non-covalent interactions such as hydrogen bonding and π-π stacking at the damaged interface. In addition, pyrogallic acid itself can also polymerize and fill the gaps in the damaged parts. In this process, the calcium sulfoaluminate expansion agent that has not yet reacted completely in the powder will also participate in the reaction and generate calcium sulfonate crystals to block the gaps. Therefore, the repair of cracks is relatively complicated. The principle diagram is as follows Figure 1As shown; at the same time,. From the mechanism point of view, it can be understood as organic and inorganic dual self-repairing effects.

[0014] Beneficial effects of the present invention: The polymer cement waterproof coating of the present invention uses organic and inorganic repair agents, which can maintain the self-repairing effect of the coating film to the greatest extent, and can self-repair cracks with a width of 0.7 mm under certain conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a schematic diagram of the reaction principle of pyrogallic acid as a self-healing agent of the present invention. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with specific embodiments.

[0017] The invention discloses a wall self-repairing method based on a self-repairing polymer cement waterproof coating.

[0018] Step 1: coating molding, according to the liquid component and the solid component in a mass ratio of 1:1.5 to 1:2.5, stir evenly and then shape; Step 2: brushing, the above coating is applied to the surface to be constructed, and a coating layer is formed after drying; Step 3: aging damage, the coating layer and the water penetrated after damage, high concentration of OH — In contact, the complex supported in the layered hydrotalcite is exposed to water and high concentration of OH — Under the action of, the oxidation reaction is released, and then polymerization is formed to complete the repair and filling of the damaged area.

[0019] Among them, the preferred liquid component in this embodiment includes the following substances in mass percentage: 80%-95% acrylate emulsion, 0.1%-1% sodium salt dispersant, 0.2%-0.5% wetting agent, 0.1%-1% propylene glycol, 0.1%-0.5% defoaming agent, and the balance is water; the solid component includes the following substances in mass percentage: 10%-30% heavy calcium, 20%-50% quartz sand, 2%-10% calcium sulfoaluminate type expansion agent, 1%-10% modified hydrotalcite, and the balance is cement.

[0020] The preferred modified hydrotalcite in this embodiment is a layered hydrotalcite loaded with a complex, wherein the complex is formed by pyrogallic acid and borate.

[0021] Among them, the preferred acrylic esters and emulsions in this embodiment are at least one of styrene acrylic emulsion, pure acrylic emulsion, styrene-butadiene emulsion, and silicone acrylic emulsion.

[0022] Among them, the preferred wetting agent in this embodiment is a polyoxyethylene ether surfactant.

[0023] Among them, the preferred quartz sand particle size in this embodiment is at least one of 70-140 mesh or 100-200 mesh.

[0024] Example 1

[0025] Based on the above-mentioned repair method, this embodiment discloses a self-repairing polymer cement waterproof coating for wall self-repair, wherein the coating is composed of a liquid component and a solid component in a mass ratio of 1:1.5.

[0026] The liquid component comprises the following substances in percentage by mass: 90% styrene-acrylic emulsion, 1% sodium salt dispersant, 0.3% wetting agent, 0.2% propylene glycol, 0.3% defoaming agent and 8.2% water.

[0027] The solid components include the following substances in percentage by mass: 10% heavy calcium, 15% 70-140 mesh quartz sand, 25% 100-200 mesh quartz sand, 5% calcium sulphoaluminate expansion agent, 5% modified hydrotalcite, and 40% PO 42.5 cement.

[0028] After the above liquid and powder are mixed separately and evenly, the powder is slowly added to the liquid at a mass ratio of 1:1.5, and stirring is continued for 5 minutes. After the two are mixed evenly, the polymer cement waterproof coating is obtained, which is then scraped and applied to form a film to test its performance.

[0029] Example 2

[0030] Based on the above-mentioned repair method, this embodiment discloses a self-repairing polymer cement waterproof coating for wall self-repair, which is composed of a liquid component and a solid component in a mass ratio of 1:2.

[0031] The liquid component includes the following substances in percentage by mass: 95% pure acrylic emulsion, 0.8% sodium salt dispersant, 0.4% wetting agent, 0.5% propylene glycol, 0.3% defoaming agent and 3% water.

[0032] The solid component comprises the following substances in percentage by mass: 15% of heavy calcium, 18% of 70-140 mesh quartz sand, 30% of 100-200 mesh quartz sand, 2% of calcium sulphoaluminate expansion agent, 1% of modified hydrotalcite and 34% of PO 42.5 cement.

[0033] After the above liquid and powder are mixed separately and evenly, the powder is slowly added to the liquid in a mass ratio of 1:2, and stirring is continued for 5 minutes. After the two are mixed evenly, the polymer cement waterproof coating is obtained, which is then scraped and applied to form a film to test its performance.

[0034] Example 3

[0035] Based on the above-mentioned repair method, this embodiment discloses a self-repairing polymer cement waterproof coating for wall self-repair, which is composed of a liquid component and a solid component in a mass ratio of 1:2.

[0036] The liquid component comprises the following substances in percentage by mass: 85% of styrene-butadiene emulsion, 0.5% of sodium salt dispersant, 0.5% of wetting agent, 0.6% of propylene glycol, 0.5% of defoaming agent and 12.9% of water.

[0037] The solid components include the following substances in percentage by mass: 16% of heavy calcium, 10% of 70-140 mesh quartz sand, 26% of 100-200 mesh quartz sand, 8% of calcium sulphoaluminate expansion agent, 10% of modified hydrotalcite, and 30% of PO 42.5 cement.

[0038] After the above liquid and powder are mixed separately and evenly, the powder is slowly added to the liquid in a mass ratio of 1:2, and stirring is continued for 5 minutes. After the two are mixed evenly, the polymer cement waterproof coating is obtained, which is then scraped and applied to form a film to test its performance.

[0039] Example 4

[0040] Based on the above-mentioned repair method, this embodiment discloses a self-repairing polymer cement waterproof coating for wall self-repair, which is composed of a liquid component and a solid component in a mass ratio of 1:2.5.

[0041] The liquid component includes the following substances in percentage by mass: 80% silicone-acrylic emulsion, 0.2% sodium salt dispersant, 0.5% wetting agent, 1% propylene glycol, 0.5% defoaming agent, and 17.8% water.

[0042] The solid components include the following substances in percentage by mass: 25% of heavy calcium, 10% of 70-140 mesh quartz sand, 17% of 100-200 mesh quartz sand, 1% of calcium sulphoaluminate expansion agent, 2% of modified hydrotalcite, and 45% of PO 42.5 cement.

[0043] After the above liquid and powder are mixed separately and evenly, the powder is slowly added to the liquid at a mass ratio of 1:2.5, and stirring is continued for 5 minutes. After the two are mixed evenly, the polymer cement waterproof coating is obtained, which is then scraped and applied to form a film to test its performance.

[0044] Comparative Example 1

[0045] Based on the above-mentioned repair method, this embodiment discloses a comparative embodiment of a self-repairing polymer cement waterproof coating for wall self-repair, wherein the coating is composed of a liquid component and a solid component in a mass ratio of 1:1.5.

[0046] The liquid component comprises the following substances in percentage by mass: 90% styrene-acrylic emulsion, 1% sodium salt dispersant, 0.3% wetting agent, 0.2% propylene glycol, 0.3% defoaming agent and 8.2% water.

[0047] The solid components include the following substances in percentage by mass: 15% of heavy calcium, 15% of 70-140 mesh quartz sand, 25% of 100-200 mesh quartz sand, 5% of calcium sulphoaluminate expansion agent, and 40% of PO 42.5 cement.

[0048] After the above liquid and powder are mixed separately and evenly, the powder is slowly added to the liquid at a mass ratio of 1:1.5, and stirring is continued for 5 minutes. After the two are mixed evenly, the polymer cement waterproof coating is obtained, which is then scraped and applied to form a film to test its performance.

[0049] Comparative Example 2

[0050] Based on the above-mentioned repair method, this embodiment discloses a comparative embodiment of a self-repairing polymer cement waterproof coating for wall self-repair, wherein the coating is composed of a liquid component and a solid component in a mass ratio of 1:2.

[0051] The liquid component includes the following substances in percentage by mass: 95% pure acrylic emulsion, 0.8% sodium salt dispersant, 0.4% wetting agent, 0.5% propylene glycol, 0.3% defoaming agent and 3% water.

[0052] The solid component comprises the following substances in percentage by mass: 18% of heavy calcium, 18% of 70-140 mesh quartz sand, 30% of 100-200 mesh quartz sand, and 34% of PO 42.5 cement.

[0053] After the above liquid and powder are mixed separately and evenly, the powder is slowly added to the liquid in a mass ratio of 1:2, and stirring is continued for 5 minutes. After the two are mixed evenly, the polymer cement waterproof coating is obtained, which is then scraped and applied to form a film to test its performance.

[0054] The examples 1-4 and the comparative examples 1-2 were cured according to the standard of "GB / T 23445-2009 Polymer Cement Waterproof Coating", and then a 10 mm long and 0.7 mm wide crack was cut on the waterproof coating with a blade, and a 300 mm high water column was maintained on one side of the coating to cause leakage at the crack and water droplets fell drop by drop. The test results are shown in the following table.

[0055] Table 1 Self-repairing of polymer cement waterproof coating

[0056]

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and modifications without departing from the concept of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A wall self-repairing method based on a self-repairing polymer cement waterproof coating, characterized in that: Step 1, coating molding, according to the liquid component and the solid component according to the mass ratio of 1:1.5~1:2.5, the proportion is mixed and the molding is carried out after being evenly stirred; the liquid component includes the following substances in mass percentage: 80%-95% of acrylate emulsion, 0.1%-1% of sodium salt dispersant, 0.2%-0.5% of wetting agent, 0.1%-1% of propylene glycol, 0.1%-0.5% of defoaming agent, and the balance is water; the solid component includes the following substances in mass percentage: 10%-30% of heavy calcium, 20%-50% of quartz sand, 2%-10% of calcium sulfoaluminate expansion agent, 1%-10% of modified hydrotalcite, and the balance is cement; the modified hydrotalcite adopts layered hydrotalcite loaded with complex, wherein the complex is formed by pyrogallic acid and borate; Step 2: Apply the coating to the surface to be constructed, and form a coating layer after drying. Step three, aging damage, the coating layer comes into contact with the water and high concentration of OH- that penetrate after the damage, and the complex loaded in the layered hydrotalcite is released under the action of water and high concentration of OH- to form an oxidation reaction, forming a polymerization to complete the repair and filling of the damaged area.

2. A wall self-repairing method based on a self-repairing polymer cement waterproof coating according to claim 1, characterized in that: The acrylic emulsion is at least one of styrene acrylic emulsion, pure acrylic emulsion, styrene butadiene emulsion and silicone acrylic emulsion.

3. A wall self-repairing method based on a self-repairing polymer cement waterproof coating according to claim 1, characterized in that: The wetting agent is a polyoxyethylene ether surfactant.

4. A wall self-repairing method based on a self-repairing polymer cement waterproof coating according to claim 1, characterized in that: The quartz sand particle size is at least one of 70-140 meshes or 100-200 meshes.

Citation Information

Patent Citations

  • Patching material for building tear and construction process thereof

    CN101402518A

  • Self-repairing organic coating applied to gathering pipeline and preparation method of self-repairing organic coating

    CN103360907A